Methyl 4-pyridyl ketone thiosemicarbazone (4-PT) as an effective and safe inhibitor of mushroom tyrosinase and antibrowning agent - Nur Amanina, Hassanuddin; Erna, Normaya; Hakimah, Ismail; Anwar, Iqbal; Mohd Bijarimi, Mat Piah; Shafida, Abd Hamid; Mohammad Norazmi, Ahmad (Elsevier B.V., 2024)
Enzymatic browning is of concern as it can affect food safety and quality. In this study, an effective and safe tyrosinase inhibitor and anti-browning agent, methyl 4-pyridyl ketone thiosemicarbazone (4-PT), was synthesised and characterised using Fourier-transform infrared (FTIR) spectroscopy, CHNS elemental analysis, and proton (1H) and carbon-13 (13C) nuclear magnetic resonance (NMR) spectroscopy. The vibrational frequencies of 4-PT were studied theoretically using vibrational energy distribution analysis (VEDA). Density functional theory (DFT) was applied to elucidate its chemical properties, including the Mulliken atomic charges, molecular electrostatic potential (MEP), quantum theory of atoms in molecules (QTAIM) and reduced density gradient non-covalent interactions (RDG-NCIs). Moreover, 4-PT was compared with kojic acid in terms of its effectiveness as a tyrosinase inhibitor and anti-browning agent. The toxicity and physicochemical properties of 4-PT were predicted via ADME evaluation, which proved that 4-PT is safer than kojic acid. Experimentally, 4-PT (IC50 = 5.82 μM, browning index (10 days) = 0.292 ± 0.002) was proven to be an effective tyrosinase inhibitor and anti-browning agent compared to kojic acid (IC50 = 128.17 μM, browning index (10 days) = 0.332 ± 0.002). Furthermore, kinetic analyses indicated that the type of tyrosinase inhibition is a mixed inhibition, with Km and Vmax values of 0.85 mM and 2.78 E-09 μM/s, respectively. Finally, the mechanism of 4-PT for tyrosinase inhibition was proven by 1D, second derivative and 2D IR spectroscopy, molecular docking and molecular dynamic simulation approaches.